PEMBATALAN SERTIFIKAT HAK ATAS TANAH KARENA PUTUSAN PENGADILAN YANG BERKEKUATAN HUKUM TETAP (INKRACHT VAN GEWIJSDE) (Studi Kasus Perkara Perdata Nomor 93/Pdt.G/2000/PN.Smda Juncto Nomor 48/Pdt/2004/PT.KT.Smda Juncto Nomor 74 K/Pdt/2005) - Burhan Nur Prasetya (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe disclosure of cases relating to a lawsuit against the holder of the certificate by the original land holder has raised the insecurity of the certificate holder. In the city of Samarinda precisely in Jalan Ir. H. Juanda RT 02 Sidodadi Urban Village, Samarinda Ulu Sub-district, Samarinda City, land dispute occurred in civil case at Samarinda District Court Number. 93 / Pdt.G / 2000 / PN.Smda Juncto Number 48 / Pdt / 2004 / PT.KT. Smda Juncto Number. 74 / Pdt / 2005, used as the basis for the cancellation of Certificate of Property Number 2853 / Kelurahan Sidodadi, 2856 / Kelurahan Sidodadi, 2857 / Kelurahan Sidodadi, 2858 / Sidodadi Urban Village, 2859 / Sidodadi Urban Village, 2860 / Sidodadi Urban Village, 2862 / Kelurahan Sidodadi The Land Office of Samarinda City is forwarded to the Regional Office of the National Land Agency of East Kalimantan Province to subsequently issue a Decree of the Head of Regional Office of the National Land Agency of East Kalimantan Province regarding the cancellation of the Certificate as the execution of the decision of the Courts which has obtained permanent legal force.Under this circumstance, the writer encourages the writer to know what the legal considerations of the Court of Samarinda are in Decision Number 93 / Pdt.G / 2000 / PN.Smda that cancels the Certificate of Property Number 2853 / Kelurahan Sidodadi, 2856 / Kelurahan Sidodadi, 2857 / Kelurahan Sidodadi, 2858 / Sidodadi urban village, 2859 / Sidodadi urban village, 2860 / Sidodadi urban village, 2862 / Kelurahan Sidodadi and to find out what effect the law has on the Certificate of Property Owned by the Court and permanent law force. This research uses a normative sociological approach, referring to the truth obtained from a reality in the field that is linked to the legal aspect.From the research result it can be seen that the legal considerations of the Samarinda Court strengthen to grant the request for the cancellation of the Certificate of the Property and the legal consequences to the Certificate which have been subsequently terminated. The court which has obtained permanent legal force (Inkracht Van Gewijsde) is null and void by the Head of Office The territory of the National Land Agency of East Kalimantan Province Number 38 / KEP-64 / IV / 2016 which is further processed by the Land Office of Samarinda City, and to avoid land disputes such as this case case, / public complaints as an effort to protect the law of Land Rights.Keywords: Cancellation of Certificate of Property.